Living Wages as Life Boat to Rescue Fairtrade’s Values for Hired Labor? The Case of Indian Tea Plantations - Kister, Jutta; Wenner, Miriam (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
Fair Trade is a normative concept for creating more “ just” trading relations between producers in the Global South and consumers in the Global North. It aims to foster the sustainable development of producers through instruments like minimum prices, long-term partnerships, and labor and environmental standards. However, as a market-based instrument, Fair Trade cannot fully escape capitalist logics like price competition. This is especially true of “Fairtrade”-certified products that compete with conventional products in supermarkets. Furthermore, as more large-scale enterprises like plantations are certified, questions emerge about how much workers actually benefit from certification. We understand Fairtrade’s recent living wages policy as a response to this critique and examine how Fairtrade attempts to address the contradictions between its alternative, moral mission and conventional market logic through the instrument of living wages play out in the hired labor context. We draw on moral geography to frame our understanding of fairness as the outcome of a contested process in which different actors assume responsibility. We combine this process-oriented approach to fairness with an understanding of shared responsibility derived from differently situated actors’ capacity to generate change. We illustrate the practical challenges of implementing universal concepts like fairness in the arena of wage setting at certified Indian tea plantations. The case reveals Fairtrade’s limited capacity to make a difference, especially pertaining to workers’ representation. The question of who is responsible for establishing fairness and on what level it should be done remains unsolved.